The exhaustive concordance of the Bible - Strong, James, 1822-1894 (MacDonald, 1890)
Includes concordance with appendix, Hebrew and Chaldee dictionary and Greek dictionary of the New Testament.
Reprint of the original.
Keywords: Bible -- dictionaries, concordances, etc